Effect of nano black rice husk ash on the chemical and physical properties of porous concrete pavement - Putra Jaya, Ramadhansyah; Haryati, Awang; Mohamad Idris, Ali; Mohd Fadzil, Arshad; Mohd Ibrahim, Mohd Yusak; Mohd Rosli, Hainin; Mohd Haziman, Wan Ibrahim (2018)
Black rice husk is a waste from this agriculture industry. It has been found that majority inorganic element in rice husk is silica. In this study, the effect of Nano from black rice husk ash (BRHA) on the chemical and physical properties of concrete pavement was investigated. The BRHA produced from uncontrolled burning at rice factory was taken. It was then been ground using laboratory mill with steel balls and steel rods. Four different grinding grades of BRHA were examined. A rice husk ash dosage of 10% by weight of binder was used throughout the experiments. The chemical and physical properties of the Nano BRHA mixtures were evaluated using fineness test, X-ray Fluorescence spectrometer (XRF) and X-ray diffraction (XRD). In addition, the compressive strength test was used to evaluate the performance of porous concrete pavement. Generally, the results show that the optimum grinding time was 63 hours. The result also indicated that the use of Nano black rice husk ash ground for 63hours produced concrete with good strength.